Perseverance of Perverse Subsidies and their Impact on Trade and the Environment - Cees van Beers; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2000)
Theoretical and empirical aspects of policy failures due to subsidies are discussed in the context of international trade. A general classification of subsidies that cause environmental externalities is presented. The economic and environmental impacts of producer subsidies on international trade are examined with partial equilibrium analysis. The magnitude and economic and environmental relevance of subsidies in various sectors is assessed on the basis of empirical indicators. Finally, suggestions are provided on how subsidy-related policy failures can be eliminated at national and international levels.
Keywords: 330; Environmental policy; Trade policy; Perverse subsidies; International institutions; International agreements; Policy failures; International trade; Environmentally damaging subsidies; Subvention; Umweltpolitik; Außenhandel; Theorie